2011
DOI: 10.1177/0333102410391486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of cluster headaches in Japan: Low prevalence of chronic cluster headache, and uncoupling of sense and behaviour of restlessness

Abstract: Japanese patients in this study showed a relatively low prevalence of chronic cluster headaches, and uncoupling of a sense of restlessness and restless behaviour. These features of cluster headache may be more common in Japanese and Taiwanese patients than in Caucasian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
60
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 22 publications
25
60
2
Order By: Relevance
“…Rozen et al [6] in a clinic based study in the USA noted two peaks of age of onset in women in their 2nd and 5th decade of life and prior studies by Peatfield et al [9] (2nd and 5th decade) and Kudrow [10] (3rd and 6th decade) noted the same finding. A recent investigation from Asia also showed this same bimodal age peaks in women with a major peak at 10-19 years and a second smaller peak of CH onset at 60-69 years [11]. Overall our survey study, which is the largest to look at gender differences of age of onset, reaffirms past and recent findings that female CH is more likely to start before 20 years of age with a second peak of onset after age 50 years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Rozen et al [6] in a clinic based study in the USA noted two peaks of age of onset in women in their 2nd and 5th decade of life and prior studies by Peatfield et al [9] (2nd and 5th decade) and Kudrow [10] (3rd and 6th decade) noted the same finding. A recent investigation from Asia also showed this same bimodal age peaks in women with a major peak at 10-19 years and a second smaller peak of CH onset at 60-69 years [11]. Overall our survey study, which is the largest to look at gender differences of age of onset, reaffirms past and recent findings that female CH is more likely to start before 20 years of age with a second peak of onset after age 50 years.…”
Section: Discussionsupporting
confidence: 88%
“…In the Manzoni et al [7] study only nausea significantly occurred more often in women than men, while the remainder of cranial autonomic and migrainous associated symptoms had no distinct gender differences. A recent study from Asia involving 68 men and 18 women noted a female predominance for some cranial autonomic symptoms including lacrimation and conjunctival injection, as well as all migrainous symptoms (nausea, vomiting, photophobia and phonophobia) [11]. Overall across the globe female CH is more likely to have migrainous associated symptoms, while males are more likely to have cranial autonomic symptoms except possibly in Japan although this study had a very small number of female CH patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This study was conducted based on the ICHD-3β criteria and could not include a sufficient number of patients with chronic CH to analyze the impact of chronic CH. Similar to this study, the frequency of chronic CH has been reported at 3.5% in Japan [22]. These data reflect a substantial job burden for Asian patients with CH, despite the low proportion of patients with chronic CH.…”
Section: Discussionsupporting
confidence: 88%
“…The fact might be attributed to regional and racial reasons. For cluster headache, the male: female ratio was 6.5∶1, which was similar to results from Taiwanese (6.4∶1) [16] and Japanese (3.8∶1) [17].…”
Section: Discussionsupporting
confidence: 84%